What went wrong? case histories of process plant disasters and how they could have been avoided - Kletz, Trevor A. (Gulf Professional Pub., 2009)
"The history of the process industries shows that many incidents are repeated after a lapse of a few years. People move on, and the lessons are forgotten. This book will help keep the memories alive"--P. xix.
Keywords: Chemical plants -- Accidents.; elektronické knihy; electronic books